Advanced injection molding technologies - Chen, Shia-Chung; Turng, Lih-Sheng; Ameli, Amir; Cabrera, Eusebio; Castro, Jose M.; Chang, Rong-Yeu; Chen, Shia-Chung; Gao, Furong; Huang, Chao-Tsai; Jong, Wen-Ren; Lee, L. James 1950-; Liu, Shih-Jung, 1964-; et al. (Hanser Publishers ; Hanser Publications, 2019)
"This book covers the most recent and important developments in advanced injection molding technologies, such as intelligent process control; technology innovations and computer simulation for emerging special injection molding processes like microinjection molding, microcellular injection molding, water-assisted foaming, water-assisted injection molding, and variable mold temperature technologies; conductive polymer foams and composites; injection molding of optical products; and an automated mold design navigation system with integrated knowledge management capability. It is intended to be used as a textbook for both introductory and advanced injection molding courses, as a must-have reference for professional engineers and engineering managers who want to keep abreast of the latest technological developments and applications, and in libraries to serve interested readers from both academic and industrial communities as well as the general public. With chapters written by an international team of experts, this book provides a broad and insightful coverage, complementary to other books on injection molding"--Resumé vydavatele
Keywords: vstřikování plastů; injection moulding; monografie; monographs